The Root of Soft Skills: Shifting the Paradigm on Success - Aries Musnandar (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2020)
The research itself was approached through a multi-case study within the qualitative method. The main instrument in qualitative method was a researcher himself which collected the data from three activities such as interview, observation as well as documentation study. The result of this study has shown that soft skills are a crucial aspect for enhancing individual performance. Although, in formal education found that academics or hard skills have become main priority in school and formal education institutions. Thence, most efforts in education best practices always pay attention to the hard skills rather than soft skills. In fact, some researches shown that soft skills are important and crucial aspect to be improved in order to increase the understanding of hard skills or technical matters. Despite of the national education policy admitted indirectly that soft skills are a priority but in field and practices not all stakeholders such as teacher and school principals implement the best program to improve soft skills instead of hard skills.